OC-047 Epigenetic alterations at diagnosis predict susceptibility, prognosis and treatment escalation in inflammatory bowel disease – ibd character. (17th June 2017) - Kalla, R; Adams, AT; Vatn, S; Bonfiglio, F; Nimmo, ER; Kennedy, NA; Ventham, N; Vatn, MH; Ricanek, P; Bergemalm, D; Halfvarson, J; Soderholm, JD; et al.
Abstract : Introduction: Biomarker discovery to predict disease outcomes is a key focus in Inflammatory Bowel Disease (IBD). We have characterised disease-associated methylation changes in newly diagnosed IBD, defined the relationship to genetic variation (meQTL) and assessed its prognostic utility in IBD. Method: Genome-wide methylation and genotyping were performed in 641 peripheral blood DNA samples (298 controls, 150 CD, 167 UC, 26 IBDU) using the Illumina 450k and HumanOmniExpressExome-8 BeadChips respectively. Covariates included age, sex, and cell counts, deconvoluted by the Houseman method. Samples were obtained from new IBD cases across Europe and outcome data were recorded. Treatment escalation in IBD was defined as the need for surgery and/or biologic therapies after initial induction of disease remission. Results: 290 probes exhibited Holm significant IBD-associated methylation differences, including MIR21 (p=7.5×10 -14 ), RPS6KA2 (1.1×10 -19 ) and PHOSPHO1 (2.5×10 -10 ) and were consistent within the European cohort. Only one probe differentiated UC from CD (NAV2, holm p=0.04).Paired genetic and methylation data showed 1037 Bonferroni significant MeQTLs indicating a genetic influence on several key loci:RPS6KA2 (8.6×10 -34 ), ITGB2 (3.3×10 -38 )and MIR21 (rs8078424, p=4.4×10 -25, rs10853015, p=7.4×10 -21 ). Follow up data were available for 214 patients with IBD and 49 patients required treatment escalation. 11 DMPs predicted treatment escalation(top probe holm p=0.003). Unsupervised linear discriminant consensus clustering were performed using 6 randomly selected top probes, identifying 2 patient subgroups with significantly different disease courses (Image;HR 10.5, 95% CI: 4.3–25.6; p=1.5×10 -24 ), outperforming conventional biomarkers in predicting treatment escalation (hsCRP >4 mg/L, HR 3.2 (1.7–5.8), p=0.0004 and Alb <36 g/L, HR 2.9 (1.5–5.6), p=0.0001). Conclusion: These data allow profiling of the IBD methylome, involving novel associations and important unequivocal replication of recent discoveries (1) and provide insight into germline variation of epigenetic mechanisms in IBD. As biomarkers, the methylome shows promise in predicting disease course in IBD. Reference: . Ventham NT, et al. Integrative epigenome-wide analysis demonstrate DNA methylation may mediate genetic risk in Inflammatory Bowel Disease. Nat. Commun. 2016:25(7)13507. Disclosure of Interest: None Declared